Projevy nepietního způsobu ukládání mrtvých u středověkých populací - Lucie Čulíková (AntropoWebzin)
In this study is collected a number of existing pieces of knowledge about substandard treatment with the dead bodies. There are also discussed the reasons which led the society to these acts. These persons were the revenants (e. g.: vampire, suicide, executed person, criminal, witch, etc.). Large part of this study is dedicated to the factual graves where the relics of these persons were found. Database of non-reverent treated persons was created on the literature basis. Via this database were e.g. traced the most frequent locations of the revenants in the certain section of the areas. There was reached the conclusion that the most frequent location was the eastern section. The next conclusion was that 62 % of the recognized persons were men. The most frequented position of the bodies was a supine position. The artifacts were found only in a few cases. There were closely followed the substandard hits on the dead bodies. The database indicated that the most frequented hits were on the legs and the hits on head and arms were frequently, too. The tendency of this work was to get and organize the pieces of knowledge found in literature and to be a certain benefit in the broad issues.